2018
DOI: 10.19044/esj.2018.v14n33p202
|View full text |Cite
|
Sign up to set email alerts
|

Importance Des Produits Forestiers Non Ligneux Medicinaux D’origine Vegetale Et Impacts Des Activites Anthropiques Sur Leur Durabilite Dans Le Sud-Ouest De La Republique Centrafricaine

Abstract: The forest in the south-west of the Central African Republic has enormous potential for non-timber forest products (NTFPs) of plant origin. The objective of this study is to identify the medicinal value of these NTFPs of plant origin with high health potential and the effects of human activities on their sustainability. The study was carried out in 09 villages in the intervention zone of the Kadéi Forestry Company. From various methodological approaches (ethno botanical survey, participant observation, invento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Plant-based NTFPs are harvested in the form of leaves, barks, fruits, sap, stems, and roots, and the frequency of harvesting is often determined by the needs associated with each NTFP. The same constant was made by [38] for whom barks were more used in traditional medicine. Depending on whether it is one part or another and the size of the individual, harvesters' resort to several modes of removal, some of which are destructive.…”
Section: Inventory Of Ntfps Their Types Of Use and Organs Used And Po...mentioning
confidence: 95%
See 1 more Smart Citation
“…Plant-based NTFPs are harvested in the form of leaves, barks, fruits, sap, stems, and roots, and the frequency of harvesting is often determined by the needs associated with each NTFP. The same constant was made by [38] for whom barks were more used in traditional medicine. Depending on whether it is one part or another and the size of the individual, harvesters' resort to several modes of removal, some of which are destructive.…”
Section: Inventory Of Ntfps Their Types Of Use and Organs Used And Po...mentioning
confidence: 95%
“…Indeed, root and bark harvesting may have more negative ecological consequences than fruit or leaf harvesting; however, fruit or leaf harvesting may also have an impact on the natural regeneration process and species conservation [38]. [39] show that using NTFP trees for food, medicine, and root harvesting, increases the likelihood of an NTFP tree absence and the high density of species, and collections of fruit, leaf, and resin decrease the likelihood of an NTFP tree absence.…”
Section: Inventory Of Ntfps Their Types Of Use and Organs Used And Po...mentioning
confidence: 99%
“…As a result, the concept of privately owned tree crops producing Agroforestry Tree Products (AFTPs) has been proposed to distinguish them from common-property forest resources [207]. This is important, as these tree products are the backbone of most rural economies and contribute to the enhancement of the socio-economic welfare of forestdependent communities [180,187,189,191,[208][209][210][211][212][213][214][215][216][217][218][219][220][221][222][223][224]. Furthermore, studies have demonstrated that the sustainable exploitation, commercialization and management of NTFPs/AFTPs could contribute immensely to the attainment of important Sustainable Development Goals (SDGs) such as SDG 2 (zero hunger), SDG 3 (good health and wellbeing), SDG 13 (climate action) and SDG 15 (life on land) [21,[225][226][227].…”
Section: Governance Issuesmentioning
confidence: 99%
“…In addition to providing essential nutrients, many tree products have medicinal properties [222,[337][338][339][340]. For example, the seeds of I. gabonensis show antimicrobial and antioxidant activities [341,342], as well as the ability to improve liver and kidney functions.…”
Section: Medicinal Value Of Wild Non-timber Forest Productsmentioning
confidence: 99%
“…Le Tableau 4 présente toutes les essences forestières exploitables présentes dans la forêt de recherche de la station de valorisation Agricole IRAD à Abong Mbang. Le Tableau 5 quant à lui illustre sur la base des travaux de prospection, layonnage et comptage, la contenance de la forêt soumise à notre étude Ce qui démontre que l'utilisation des PFNL à une valeur culturel(Zima et al, 2018). Il présente la superficie distribuée dans chacune des strates, les classes de diamètre et le volume réel existent dans chacune des strates.…”
unclassified